HOME DOOR AUTOMATION SYSTEM - SIDDHARTH B R; RAVI RANJAN; JASMINEPEMEENAPRIYADARISINI M (International Journal of Innovations in Engineering Research and Technology, 2021)
Our fundamental target is to use the distinctive electronic parts accessible in the market and fabricate a coordinated home security framework by utilizing Bluetooth gadget and Microcontroller innovation. This framework gives benefit with ease thought about to the cost of the accessible security framework. We need to make a framework that will give 24 into 7-benefit .By utilizing enlisted secret word in this framework we can open the entryway by which it builds the security level to keep an unapproved opening. In the event that the client overlooks the blend of secret key this framework gives the adaptability to the client to change or reset the password. Safety effort is high as gave in two ways. To start with, we need to enter secret key for verification by Arduino association and second is for opening the entryway in application. The two passwords can be changed as and when required. This programmed password based bolt framework will give client more secure and minimal effort method for locking-opening framework. The security door lock automation system promises a bold step to the future where mechanical door locks will be substituted by electronic door locks